STUDENTS OF TEACHER EDUCATION IN HUNGARY BEFORE AND DURING THE BOLOGNA PROCESS - JANCSÁK, Csaba (2018)
In the past decade, several system-level changes havetaken place in Hungarian higher education: universityintegration was realized, the credit system was introduced, thepreselection-type admission system ceased to exist and teachereducation was changed into a two-cycle education. New placesof education and new, markedly different, forms of educationhave appeared, and the number of students admitted intoinstitutes of higher education has increased significantly. Thesocio-politico-economic changes happening since thebeginning of the 90s have made a significant impact on theworld of public education as well (de-politicization ofeducation, pluralism in selecting schools, decentralization ofthe administrative background of education, the formation ofschool autonomy, etc.). The drive behind these changes werethe modern tendencies of economy and educational policy and,moreover, young people and their parents.